KEPEMIMPINAN WANITA DALAM MANAJEMEN KEPENDIDIKAN - Halilah, Halilah (977-2442404)
Leadership of the principal is really crucial to the development of a harmonious teamwork of teachers, staff and students in the school. A good school leadership can influence the work environment to be pleasant and comfortable, the teachers can teach students very well and the student can enjoy their study -that ultimately influence the professional development among teachers. The key to success of a school lies in the efficiency and effectiveness of the appearance of a school principal. Leadership style of women is able to create an effective leadership because women have a special quality to create organizational effectiveness. Keywords: Leadership, Leadership Style, Womens Leadership as a School PrincipalsÂ Kepemimpinan seorang kepala sekolah sangat menentukan berkembangnya semangat kerjasama yang harmonis bagi para guru, staf maupun siswa. kepemimpinan kepala sekolah yang baik dapat mempengaruhi suasana kerja yang menyenangkan dan nyaman, para guru dapat menjalankan tugas mengajar dengan baik dan siswa dapat belajar dengan senang dan tertib yang akhirnya berpengaruh terhadap perkembangan profesional diantara guru. Kunci keberhasilan suatu sekolah pada hakikatnya terletak pada efisiensi dan efektivitas penampilan seorang kepala sekolah. Gaya kepemimpinan kepala sekolah wanita mampu mewujudkan kepemimpinan yang efektif karena wanita mempunyai keunggulan dalam memerankan dan menciptakan efektivitas organisasi.Â Kata Kunci: Kepemimpinan, Gaya Kepemimpinan, Kepemimpinan Kepala Sekolah Wanita